Practices for making residents' wishes fit institutional constraints: a case of manipulation in dementia care. (2nd January 2019) - Kristiansen, Elisabeth Dalby; Rasmussen, Gitte; Andersen, Elisabeth Muth
Abstract: Purpose: The study aims to show how practices of manipulation are used by a member of staff in a care situation where the member of staff has to perform two tasks at once. Method: The study is an ethnomethodological conversation analytic single-case study of a care situation in residential dementia care. The analyses are based on video recordings and observations conducted during 9 months of fieldwork at a residential care facility for persons with dementia. Results: The study details the methods by which a member of staff engages in manipulation by constructing her actions as responses to a resident's wish which has in fact never been stated. Conclusion: The study discusses how manipulation may be understood as care staff practices for making a residents' wishes fit the institutional constraints they are subjected to and for "doing what is best for the resident."